Conductivity in carbon nanotube polymer composites: A comparison between model and experiment. (August 2016) - Castellino, Micaela; Rovere, Massimo; Shahzad, Muhammad Imran; Tagliaferro, Alberto
Graphical abstract: Abstract: Carbon nanotubes (CNTs) demonstrate remarkable conductive behaviour, which suggests promising applications. Their outstanding properties have been used in the development of CNT–polymer composites as possible alternative materials for various applications, such as flexible electrodes, antistatic coatings and piezoresistive sensors. In our study we focused our attention on the evaluation and modelling of CNT-filled epoxy resin electrical conductivity. We discuss the results with regard to the influence of CNTs dimensions and content. Exploiting the Dijkstra algorithm, we implemented a simulation code which determines the shortest route between electrodes in the polymer. The longer the path inside the polymer, the more non-conductive the composite becomes, since polymer resistivity is orders of magnitude higher than that of CNTs. We compared these simulated results with experimental data obtained at several wt% and found a good correspondence between modelling and experimental results.